Epidemiology of Toxocariasis in England and Wales. (20th February 2016) - Halsby, K.; Senyonjo, L.; Gupta, S.; Ladbury, G.; Suvari, M.; Chiodini, P.; Morgan, D.
Summary: Toxocara infection occurs through ingestion of parasite eggs excreted by dogs and cats, and can cause severe morbidity. The burden of disease in England and Wales is not well described, and the impact of public health campaigns conducted in the mid‐1990s is uncertain. This paper uses data from two extensive databases to explore the trends in this disease in England and Wales from the 1970s to 2009.